THE EFFECT OF TAX SERVICE QUALITY, TAX SANCTIONS, TAXPAYER AWARENESS AND THE USE OF TAX INCENTIVES ON TAX COMPLIANCE (Case Study on MSME Taxpayers in Subang District) - Lina Putri Selina; Indah Umiyati; Icih Icih (Journal of Taxation Analysis and Review, 2022)
This study aims to determine the effect of tax service quality, tax sanctions, taxpayer awareness and the use of tax incentives on tax compliance with a case study on MSME taxpayers in Subang Regency. This study uses quantitative methods using primary data. Data collection techniques used questionnaires that were distributed online and offline. The population in this study are taxpayers who have MSME businesses located in Subang Regency. The sampling technique used was non- probability sampling using accidental sampling procedure with a total of 103 respondents. The data test analysis technique in this study uses data quality analysis consisting of validity and reliability tests, logistic regression tests, hypothesis testing using the Wald test (partial t test) and the Omnibus test of model coefficient (simultaneous f test). The results show that simultaneously the quality of tax services, tax sanctions, and taxpayer awareness have no significant effect on tax compliance. The use of tax incentives has a significant effect on tax compliance. However, simultaneously the quality of tax services, tax sanctions, taxpayer awareness and the use of tax incentives can simultaneously affect tax compliance.